Anais Dos Seminários De Redução, Minério De Ferro E Aglomeração 2017
DOI: 10.5151/2594-357x-27003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Início De Operação Das Prensas De Rolos Do Projeto Minas-Rio

Abstract: ResumoO projeto Minas-Rio iniciou as suas operações no final de 2014 e se encontra na fase de ramp-up buscando a capacidade nominal. O circuito de cominuição inclui três prensas de rolos em circuito aberto com o objetivo de criar micro fissuras no minério e assim reduzir o consumo energético da etapa seguinte, o circuito de moagem de bolas. Este tipo de fluxograma, com prensa de rolos (circuito aberto) seguido de moagem de bolas (circuito fechado), é conhecido como circuito híbrido. A literatura apresenta este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…For the HPGR-based circuit, the proportion of ultrafine material simulated is within an acceptable range for the ore under study. Indeed, the simulated result (Table 2) is in line with the operational data published by Mazzinghy et al [45], who found that HPGR does not generate excessive ultrafine material in the Minas Rio operation. However, it is worth mentioning that those estimates are subject to uncertainty, mainly due to limitations of the comminution models for this size range and the limited information on the classification of the grinding products utilizing hydrocyclones, particularly in the case of itabirites.…”
Section: Resultssupporting
confidence: 88%
“…For the HPGR-based circuit, the proportion of ultrafine material simulated is within an acceptable range for the ore under study. Indeed, the simulated result (Table 2) is in line with the operational data published by Mazzinghy et al [45], who found that HPGR does not generate excessive ultrafine material in the Minas Rio operation. However, it is worth mentioning that those estimates are subject to uncertainty, mainly due to limitations of the comminution models for this size range and the limited information on the classification of the grinding products utilizing hydrocyclones, particularly in the case of itabirites.…”
Section: Resultssupporting
confidence: 88%